Drone x-ray / Lily Suryani Azmi Lee ... [et al.] - Azmi Lee, Lily Suryani; Mat Jusoh, Masitah; Abdul Rahim, Siti Farhana; Anuar, Nur Syazwani; Mohd Arifin, Siti Aisyah (2019)
X-Ray examinations are widely used in health sectors as a tool to help doctors to diagnose a disease. Due to the importance of x-ray examination and high demand towards the patients, x-ray machine should be flexible to ease the radiographer to perform the best radiograph. The current mobile x-ray machine is heavy and bulky to handle and sometimes can injure the radiographer due to non-ergonomic posture when handling the x-ray machine. This product is suitable in preventing radiographers exposed to possible injury and unsafe environment.